Discovery Stories of RET Fusions in Lung Cancer: A Mini-Review - Takeuchi, Kengo (Frontiers in Physiology, 2019)
In 2004, a chemical inhibitor of the kinase activity of EGFR was reported to be effective in a subset of lung cancer patients with activating somatic mutations of EGFR. It remained unclear, however, whether kinase fusion genes also play a major role in the pathogenesis of lung cancers. The discovery of the EML4-ALK fusion kinase in 2007 was a breakthrough for this situation, and kinase fusion genes now form a group of relevant targetable oncogenes in lung cancer. In this mini-review article, the discovery of RET fusions, the third kinase fusion gene in lung cancer, is briefly described.